2021
DOI: 10.1101/2021.10.20.465140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic chromosomal interactions and control of heterochromatin positioning by Ki-67

Abstract: Ki67 forms a protective layer around mitotic chromosomes and is involved in genome positioning around nucleoli during interphase. However, a lack of genomic interaction maps has hampered a detailed understanding of the role of Ki67 in chromatin organization. We used pA-DamID to map genome-Ki67 interactions in three human cell lines and throughout the cell cycle. In mitosis, Ki67 shows a surprising preference for the distal 15-30 Mb of each chromosome. Early in interphase, when Ki67 is present in pre-nucleolar … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 87 publications
3
2
0
Order By: Relevance
“…It remains to be determined whether it interacts with components of heterochromatin, including HP1α, and whether its depletion affects the abundance of these proteins within heterochromatin and, consequently, its nanoscale organisation. However, our data are consistent with a recent genome‐wide mapping study which found that Ki‐67 binds centromere‐proximal regions marked with H3K9me3 in interphase (preprint: van Schaik et al , 2021 ). Also, the ability of Ki‐67 to adapt to different chromatin environments remains to be explored.…”
Section: Discussionsupporting
confidence: 92%
“…It remains to be determined whether it interacts with components of heterochromatin, including HP1α, and whether its depletion affects the abundance of these proteins within heterochromatin and, consequently, its nanoscale organisation. However, our data are consistent with a recent genome‐wide mapping study which found that Ki‐67 binds centromere‐proximal regions marked with H3K9me3 in interphase (preprint: van Schaik et al , 2021 ). Also, the ability of Ki‐67 to adapt to different chromatin environments remains to be explored.…”
Section: Discussionsupporting
confidence: 92%
“…To compare Nanopore and Illumina-based approaches we sequenced conventional LaminB1-DamID libraries from N2A cells. LaminB1-occupancy profiles were comparable between technologies and similar to those obtained previously from mouse embryonic stem cells (mESCs) 26 ( Fig. 1f ).…”
Section: Mainsupporting
confidence: 85%
“…LaminB1-occupancy profiles were comparable between technologies and similar to those obtained previously from mouse embryonic stem cells (mESCs) 26 (Fig. 1f).…”
supporting
confidence: 85%
See 2 more Smart Citations